Palladium-catalyzed arene C–H activation/ketone C–H functionalization reaction: route to spirodihydroindenones. Issue 7 (24th April 2017) - Zhang, Bo-Sheng; Hua, Hui-Liang; Gao, Lu-Yao; Liu, Ce; Qiu, Yi-Feng; Zhou, Ping-Xin; Zhou, Zhao-Zhao; Zhao, Jia-Hui; Liang, Yong-Min
Abstract : A novel palladium and norbornene catalyzed arene C–H activation method to synthesize various spirodihydroindenone derivatives is developed. Abstract : A novel palladium and norbornene catalyzed arene C–H activation method to synthesize various spirodihydroindenone derivatives was developed. This method produces spirodihydroindenones employing aryl iodides with 2-(2-bromoethyl)-cyclopentanones via a domino reaction, which simplifies the route of building spiro compounds and expands further applications for functional groups selectivity.